Insights into the relationship between professional values and caring behavior among nurses in neonatal intensive care units - Ahmad Ayed; Moath Abu Ejheisheh; Basma Salameh; Ahmad Batran; Alaa Obeyat; Riham Melhem; Sanaa Alkhatib (BMC, 2024)
Abstract Objective Professional values are crucial for delivering high-quality care in neonatal intensive care units while caring behavior impacts nurses' performance and well-being. The purpose of this study was to assess the relationship between professional values and caring behavior among nurses in neonatal intensive care units. Methods A cross-sectional study involving 172 nurses was conducted using the Nursing Professional Value Scale and Caring Behaviors Assessment Tool. The study was carried out between 1 October and 5 December 2023. Results Nurses demonstrated a moderate to high degree of professional commitment, with a mean professional value score of 91.1 ± 11.1. The mean score for caring behavior was 99.7 ± 12.4. The highest-rated domain was setting up a supporting, protective, and corrective environment, with a mean score of 22.8 ± 2.7. A low positive relationship was found between the supportive, protective, and corrective environment domain and nurses' professional value (r = 0.18, p = 0.017), as well as between overall caring behavior and nurses' professional value (r = 0.16, p = 0.038). Conclusion The results indicate a favorable relationship between professional values and caring behavior, especially in areas like establishing a supportive workplace. However, both professional value and caring behavior needs improvement in certain aspect. Enhancing these aspects could further strengthen their relationship, ultimately improving the quality of care provided to newborn patients and their families. Practice implications To cultivate a positive work environment and instill caring behaviors and professional values among NICU nurses, it is imperative to allocate sufficient time and resources. This investment is necessary for nurturing a culture of care, improving patient outcomes, and fostering a supportive environment for NICU nurses, newborn, and their families.